A Novel Mechanism, Linked to Cell Density, Largely Controls Cell Division in Synechocystis . Issue 4 (23rd June 2017) - Esteves-Ferreira, Alberto A.; Inaba, Masami; Obata, Toshihiro; Fort, Antoine; Fleming, Gerard T.A.; Araújo, Wagner L.; Fernie, Alisdair R.; Sulpice, Ronan
Abstract : Nutrient limitation, self-shading, and quorum sensing are not major limiting factors for the growth of Synechocystis in batch cultures. Abstract: Many studies have investigated the various genetic and environmental factors regulating cyanobacterial growth. Here, we investigated the growth and metabolism of Synechocystis sp. PCC 6803 under different nitrogen sources, light intensities, and CO2 concentrations. Cells grown on urea showed the highest growth rates. However, for all conditions tested, the daily growth rates in batch cultures decreased steadily over time, and stationary phase was obtained with similar cell densities. Unexpectedly, metabolic and physiological analyses showed that growth rates during log phase were not controlled primarily by the availability of photoassimilates. Further physiological investigations indicated that nutrient limitation, quorum sensing, light quality, and light intensity (self-shading) were not the main factors responsible for the decrease in the growth rate and the onset of the stationary phase. Moreover, cell division rates in fed-batch cultures were positively correlated with the dilution rates. Hence, not only light, CO2, and nutrients can affect growth but also a cell-cell interaction. Accordingly, we propose that cell-cell interaction may be a factor responsible for the gradual decrease of growth rates in batch cultures during log phase, culminating with the onset of stationary phase.